2008
DOI: 10.1111/j.1745-459x.2008.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Serving Temperature on the Sensory Attributes of Red and White Wines

Abstract: Convention dictates that red wines should be served around room temperature and white wines should be served chilled. The objective of this study was to determine the sensory impact of white wine serving temperature (4, 10 and 18C) and red wine serving temperature (14, 18 and 23C) on wine sensory attributes. A trained panel evaluated a series of adjusted model wines served at different serving temperatures. The control white wine was adjusted to enhance sweetness and acidity, while the control red wine was adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…In our case, lowering the tasting temperature, thresholds of MNEI increased. This result is in accordance with Ross and Weller (2008) who found that sweetness and acidity intensities of white wines were significantly influenced by the interaction between the assessors and serving temperature. This result also agrees with those of Schiffman et al (2000), by which temperature affected perceived sweetness intensities, for the most part of investigated sweeteners, when they were added at the lowest concentrations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our case, lowering the tasting temperature, thresholds of MNEI increased. This result is in accordance with Ross and Weller (2008) who found that sweetness and acidity intensities of white wines were significantly influenced by the interaction between the assessors and serving temperature. This result also agrees with those of Schiffman et al (2000), by which temperature affected perceived sweetness intensities, for the most part of investigated sweeteners, when they were added at the lowest concentrations.…”
Section: Discussionsupporting
confidence: 92%
“…In our case, lowering the tasting temperature, thresholds of MNEI increased. This result is in accordance with Ross and Weller () who found that sweetness and acidity intensities of white wines were significantly influenced by the interaction between the assessors and serving temperature. This result also agrees with those of Schiffman et al .…”
Section: Discussionsupporting
confidence: 92%
“…Ross & Weller () evaluated how temperature affected attributes associated with red and white wine and concluded that serving temperature may have had a greater influence on the attributes associated with white wine than the red wine. As the temperature the white wine was served at decreased, the aroma intensity decreased.…”
Section: Resultsmentioning
confidence: 99%
“…They reported that consumer's saltiness perception varies depending on the temperature the soup product is served at; however, they stated that the saltiness perception at different serving temperatures can be modulated by dietary patterns. Ross & Weller (2007) evaluated how temperature affected attributes associated with red and white wine and concluded that serving temperature may have had a greater influence on the attributes associated with white wine than the red wine. As the temperature the white wine was served at decreased, the aroma intensity decreased.…”
Section: Full Bodymentioning
confidence: 99%
“…The phenomenon may also result from increased perception of sweetness by tasters and their ability to assess the sweet taste at different temperatures, which has recently been studied in wines (Ross and Weller, 2008). The changes in the perception of sweet taste may also be affected by the fat content of the milk or compounds derived from it (Francis et al, 2000).…”
Section: Ideal Sucrose Concentrationmentioning
confidence: 98%